Characterization and selection method of Venturi injectors for pressurized irrigation - Manzano, Juan; Palau, Carmen; Azevedo, Benito; Bomfim, Guilherme; Vasconcelos, Denise (Revista Ciência Agronômica, 2018)
Venturi-type chemigation injectors are widely used due to their advantages: they do not require electric power and are cheap to operate. However, they also generate considerable energy losses which affect the pressure in the system. The correct characterization of these systems requires pressures to be correctly set at the inlet, injector and outlet points in relation to main and injected solution flows. These analytical relationships, as described in the International Organization for Standardization’s standard ISO 15873:2002, can be obtained theoretically, although it is recommended that the manufacturer should determine the real behavior of the injector by operational tests. These relationships should also be provided graphically in the form of nomograms in order to facilitate the association of the variables involved and the subsequent selection of a specific model or class and type of assembly. In order to make the right choice, it is also necessary to have precise information on the irrigation sub-units that it feeds and the grower’s fertilization program.